Analisis Hukum Persaingan Usaha terhadap Merger Tokopedia dan TikTok Shop dalam Ekosistem Ekonomi Digital di Indonesia - Saban, Rahmatul; Nirwina; Handayani, Sri (Indonesian Journal Publisher, 2026)
The rapid development of the digital economy in Indonesia has transformed business competition, particularly in the increasingly concentrated e-commerce sector. One significant phenomenon is the merger between TikTok Shop and Tokopedia, which raises concerns regarding market structure and competitive dynamics. This study aims to analyze the merger from the perspective of Indonesian competition law, particularly under Law Number 5 of 1999. This research employs a normative legal method with a case study approach, utilizing legal documents, statutory regulations, and relevant literature. The findings indicate that the merger has the potential to increase market concentration and strengthen market power through the integration of digital ecosystems, including social commerce, user data, and network effects. However, from a legal standpoint, the merger cannot be categorized as monopolistic as long as it remains under regulatory supervision. This study contributes to the development of digital competition law by emphasizing the need for analytical approaches that extend beyond market structure to include data control and platform ecosystems. The implication is that competition authorities must adopt adaptive regulatory frameworks to address the complexities of digital markets